2006
DOI: 10.1243/09544119jeim146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contact pressure on wear and friction of ultra-high molecular weight polyethylene in multidirectional sliding

Abstract: Please cite the original version: Saikko, Vesa. 2006 All material supplied via Aaltodoc is protected by copyright and other intellectual property rights, and duplication or sale of all or part of any of the repository collections is not permitted, except that material may be duplicated by you for your research use or educational purposes in electronic or print form. You must obtain permission for any other use. Electronic or print copies may not be offered, whether for sale or otherwise to anyone who is not an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
99
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 28 publications
18
99
2
2
Order By: Relevance
“…2 c). This is within the physiological range of contact pressure in human articular joints (Saikko, 2006). The pins were machined from ram-extruded non-cross-linked (0 MRad) and highly cross-linked (10 MRad) GUR 1050 UHMWPE.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…2 c). This is within the physiological range of contact pressure in human articular joints (Saikko, 2006). The pins were machined from ram-extruded non-cross-linked (0 MRad) and highly cross-linked (10 MRad) GUR 1050 UHMWPE.…”
Section: Methodsmentioning
confidence: 94%
“…Based on Hertizan theory (Johnson 1987), the real contact area shows a nonlinear increase with the increase in load, so, the wear factor would be decreased. In another study by Saikko (2006), it was suggested that the pressure value of 2 MPa should not be exceeded in the pin-on-disc wear tests, to achieve clinically comparable wear of UHMWPE cups. Therefore, further tests need to be carried out using a lower contact pressure, within this suggested limit, to reproduce higher wear factors under a range of CSs.…”
Section: Discussionmentioning
confidence: 99%
“…The wear factor of conventional UHMWPE is highly sensitive to the type of relative motion [Saikko et al, 2004;Saikko, 2014] and contact pressure [Saikko, 2006]. With decreasing multidirectionality and increasing contact pressure, the wear factor decreases significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In [5], the polymer wear in terms of cumulative linear and volume wear when the wear factor is chosen to be a function of contact pressure was first evaluated. Herewith, various known wear factor dependencies on the contact pressure were investigated as contained in [9,10,11]. Since the contact pressure in the above formulae is a power function with a negative degree, these relations give a decrease in wear factor depending on the increase of a contact pressure, which means a reduction of wear values that are not uniquely consistent with the physics of the process.…”
Section: Introductionmentioning
confidence: 99%